DAMPAK SERIAL ANIMASI UPIN DAN IPIN PADA KOSAKATA DALAM PERCAKAPAN BAHASA INDONESIA - Barung, Rachmat; Djumingin, Sulastriningsih; Daeng, Kembong (Fakultas Teknik Universitas Negeri Makassar, 2022)
This research is a qualitative research using the animated series Upin and Ipin which aims to describe the intensity of watching, frequent vocabulary, and the impact caused by frequent viewing of the use of vocabulary in Indonesian conversation for students of SD Negeri 121 Tangsa, Baroko District, Enrekang Regency. The data of this research is the result of vocabulary imitated by students in conversation. Sources of data are 21 students as SD Negeri 121 Tangsa. Data collection techniques used are observation, documentation, interviews, and recording techniques. The results showed that; (1) there are two categories of students watching the animated series Upin Ipin, namely light and heavy viewers; (2) vocabulary that is often imitated by students, namely; (a) it's true, it's true, (b) teacher, (c) it's okay, (d) I like it, I like it, (e) various kinds of things, and (f) two singgit, two singgit, two singgit; and (3) the impact of using imitated vocabulary on students' Indonesian learning, namely; first, students can use the Malaysian language; second, students are skilled in speaking the vocabulary they have learned; third, it can improve students' social skills; and fourth, students are able to develop themselves in communicating.